Synchronizing of Stabilizing Platform Mounted on a Two-Wheeled Robot - Mohammad Rabiul Islam; Mohammad Rubaiyat Tanvir Hossain; Sajal Chandra Banik (Journal of Robotics and Control (JRC), 2021)
This paper represents the designing, building, and testing of a self-stabilizing platform mounted on a self-balancing robot. For the self-stabilizing platform, a servo motor is used and for the self-balancing robot, two dc motors are used with an encoder, inertial measurement unit, motor driver, an Arduino UNO microcontroller board. A PID controller is used to control the balancing of the system. The PID controller gains (Kp, Ki, and Kd) were evaluated experimentally. The value of the tilted angle from IMU was fed to the PID controller to control the actuated motors for balancing the system. For the self-stabilizing control part, whenever the robot tilted, it maintained the horizontal position by rotating that much in the opposite direction.